Targeted Metabolomics Shows Low Plasma Lysophosphatidylcholine 18:2 Predicts Greater Decline of Gait Speed in Older Adults: The Baltimore Longitudinal Study of Aging - Gonzalez-Freire, Marta; Moaddel, Ruin; Sun, Kai; Fabbri, Elisa; Zhang, Pingbo; Khadeer, Mohammed; Salem, Jr, Norman; Ferrucci, Luigi; Semba, Richard D (The journals of gerontology. Series A, Biological sciences and medical sciences, 2019)
Gait speed is an important measure of lower extremity physical performance in older adults and is predictive of disability and mortality. The biological pathways involved in the decline of lower extremity physical performance are not well understood. We used a targeted metabolomics approach to identify plasma metabolites predictive of change in gait speed over time. Gait speed was measured at baseline and over median follow-up of 50.5 months in 504 adults, aged ≥50 years, who had two or more study visits in the Baltimore Longitudinal Study of Aging (BLSA). Plasma metabolites were measured using targeted mass spectrometry (AbsoluteIDQ p180 Kit, Biocrates). Of 148 plasma metabolites (amino acids, biogenic amines, hexoses, glycerophospholipids) measured, eight were significantly associated with gait speed at baseline, independent of age and sex: hexoses (r = -0.148, p < .001), [sphingomyelin (SM) 16:1 (r = -0.091, p = .0009), SM 18:0 (r = -0.085, p = .002), SM 18:1 (r = -0.128, p < .0001], phosphatidylcholine aa 32:3 (r = -0.088, p = .001), lysophosphatidylcholine (LPC) 17:0 (r = 0.083, p = .003), LPC 18:1 (r = 0.089, p = .001), and LPC 18:2 (r = 0.104, p < .0001). Adjusting for baseline age, sex, and chronic diseases, baseline plasma LPC 18:2 was an independent predictor of the rate of change of gait speed over subsequent follow-up (p = .003). No other plasma metabolites were significantly associated longitudinal changes of gait speed over time. Low plasma LPC 18:2, which has previously been shown to predict impaired glucose tolerance, insulin resistance, type 2 diabetes, coronary artery disease, and memory impairment, is an independent predictor of decline in gait speed in older adults.